Revmatoidní artritida - Šenolt, Ladislav (Vnitrni lekarstvi, 2018)
Rheumatoid arthritis is an autoimmune disease manifested by a persistent inflammation of synovial joints, bone destruction, loss of cartilage and increased risk of cardiovascular and other intercurrent diseases. The treatment of rheumatoid arthritis should be based on the strategy of treat to target therapy which is achieving remission, in some cases low activity of the disease. Essential to the treat to target therapy are more frequent checkups and optimization of treatment based on disease activity. Methotrexate continues to be the essential medicine from the group of disease modifying antirheumatic drugs for rheumatoid arthritis treatment. At the start are frequently added glucocorticoids. If the effect is insufficient, biological therapy or use of targeted synthetic drugs can be considered. In this overview, the author will focus on epidemiology and risk factors, pathophysiology and in particular on the diagnostics, evaluation of activity and treatment of rheumatoid arthritis.Key words: diagnostics - disease activity - rheumatoid arthritis - treatment.
Keywords: Antirheumatic Agents; výsledek terapie; antirevmatika; kombinovaná farmakoterapie; methotrexát; Treatment Outcome; revmatoidní artritida; Arthritis, Rheumatoid; lidé; indukce remise; Humans; Drug Therapy, Combination; Methotrexate; Remission Induction